BOLAJAQ FIZIKA OQÍTÍWSHÍLARÍNÍŃ METODIKALÍQ TAYARLÍǴÍN JETILISTIRIW FAKTORLARÍ - Isakova, M.I. (SCIENCE and SOCIETY, 2024)
This article provides information on the factors of improving the knowledge of future physics teachers, that is, improving their methodological training through the use of innovative technologies in the educational process according to the international assessment PISA.